Therapeutic Effects of Hydralazine on Renal Ischemia-Reperfusion Injury in Rat. - Ahmadi, Fatemeh; Hajihashemi, Saeed; Rahbari, Ali; Ghanbari, Fatemeh (Journal of Contemporary Medical Sciences, 2019)
Objective: Renal ischemia-reperfusion (I-R) induces acute kidney injury (AKI). In this study, the effect of hydralazine was investigated on the renal injury induced by the I-R in rats. Methods: AKI was induced with bilateral obstruction of the renal artery and vein for 20 minutes following with 24 hours of reperfusion. Hydralazine (5mg/kg) was injected intraperitoneally as post- treatment. Results: Hydralazine significantly increased the levels of renal clearance of creatinine and renal blood flow, while was decreasing by I-R. Also, hydralazine significantly improved levels of serum electrolytes (sodium and potassium) that were impaired by I-R. The tissue MDA levels were significantly suppressed by hydralazine. Conclusion: According to the results, the post treatment of hydralazine had a therapeutic effect on renal ischemia-reperfusion because improved ion reabsorption and excretion and increased renal blood flow and glomerular filtration rate and decreased lipid peroxidation.